The effect of financial distress on accounting misstatements during the Covid-19 pandemic - Akhmad Sigit Adiwibowo; Putri Nurmala (The Indonesian Accounting Review, 2024)
This study aims to examine the effect of financial distress on accounting misstatements and to find out whether the COVID-19 pandemic moderates the relationship between financial distress and accounting misstatements. This study uses data from property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period from 2017 to 2021. The total research sample is 145 entities. The statistical methodology used in this study is panel regression analysis with the following steps: selecting the best regression model, classical assumption testing, and regression testing to determine coefficient values and significance levels. The results of this study show that financial distress has no significant effect on accounting misstatements. This study also finds empirical evidence that the COVID-19 pandemic does not moderate the relationship between financial distress and accounting misstatement. Although accounting misstatements have been a research topic for many years, little attention has been paid to their impact on companies experiencing financial distress and crises. Further research still needs to be carried out regarding the impact of the COVID-19 pandemic on the relationship between financial distress and accounting misstatement using a sample of companies that have a high multiplier effect. It is hoped that the results of this study can provide additional references to prove that agency theory and prospect theory can explain accounting misstatements.